Mindfulness During the COVID-19 Pandemic Lockdowns: Intolerance Uncertainty and Psychological Well-Being Among Employees - Irak, Doruk Uysal; Dede, Beyza; Demir, Nehir (SAGE PUBLICATIONS INC, 2024)
The COVID-19 pandemic has increased uncertainty worldwide, which has various negative impacts on psychological well-being. In times like these, it is important to explore how individual resources such as trait mindfulness would help people deal with uncertainty. The aim of the current study was to examine the role of intolerance to uncertainty (IU) as a mediator between trait mindfulness and psychological well-being, including stress, anxiety, depression, and emotional burnout, among employees. Two hundred ninety-three employees completed an online self-report questionnaire during the first COVID-19 pandemic lockdowns in Turkey. The nonparametric bootstrap procedure in AMOS 26.0 was used to test the proposed model. The findings indicated full mediation between trait mindfulness and psychological well-being measures among employees. In other words, employees who reported higher levels of mindfulness perceived their current situation as less threatening, and they were able to tolerate uncertainty, which decreased participants' stress, anxiety, depression, and emotional burnout. The findings are important for understanding the impact of mindfulness on the psychological well-being of people and the role of intolerance uncertainty in this relationship. The results will be useful for the development of new interventions to promote resources that will increase individual awareness and control during difficult circumstances. The COVID-19 pandemic has increased uncertainty worldwide, which has various negative impacts on psychological well-being. However, little is known about the role of uncertainty during the pandemic and possible resources, such as mindfulness which might be helpful during difficult times. This study aims to explore how individual resources such as trait mindfulness would help people deal with uncertainty during the Covid-19 pandemic. Two hundred ninety-three employees completed an online self-report questionnaire during the first COVID-19 pandemic lockdowns in Turkey. According to the study, employees who reported higher levels of mindfulness perceived their current situation as less threatening and could tolerate uncertainty, which decreased participants' stress, anxiety, depression and emotional burnout. The findings are important for understanding the impact of mindfulness on psychological well-being and the role of intolerance uncertainty in this relationship. The results will be useful for developing new interventions to promote resources that will increase individual awareness and control during difficult circumstances.
Keywords: mindfulness; intolerance to uncertainty; employee well-being; psychological well-being; COVID-19 pandemic; MENTAL-HEALTH; DEPRESSION ANXIETY; TRAIT MINDFULNESS; RESPONSES; BENEFITS; IMPACT; MODEL; WORK; ATTENTION; SYMPTOMS; Social Sciences - Other Topics